2018
DOI: 10.15252/embj.201797786
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of wound angiogenesis reveals macrophage orchestrated vessel sprouting and regression

Abstract: Wound angiogenesis is an integral part of tissue repair and is impaired in many pathologies of healing. Here, we investigate the cellular interactions between innate immune cells and endothelial cells at wounds that drive neoangiogenic sprouting in real time and in vivo. Our studies in mouse and zebrafish wounds indicate that macrophages are drawn to wound blood vessels soon after injury and are intimately associated throughout the repair process and that macrophage ablation results in impaired neoangiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
220
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(244 citation statements)
references
References 79 publications
18
220
1
5
Order By: Relevance
“…In nontumoral processes, vascular remodeling takes place after angiogenesis to produce a functional network. This process, referred to as post‐angiogenesis or vascular maturation, involves an integrated series of vascular activities, including inter alia, arteriovenous specification, vessel pruning, new vessel coverage by mature pericytes, and, in some tissues, the formation of a hierarchical network of vessels based on diameters . Although angiogenesis stricto sensu has been extensively studied, especially in cancer, post‐angiogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nontumoral processes, vascular remodeling takes place after angiogenesis to produce a functional network. This process, referred to as post‐angiogenesis or vascular maturation, involves an integrated series of vascular activities, including inter alia, arteriovenous specification, vessel pruning, new vessel coverage by mature pericytes, and, in some tissues, the formation of a hierarchical network of vessels based on diameters . Although angiogenesis stricto sensu has been extensively studied, especially in cancer, post‐angiogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This process, referred to as post-angiogenesis or vascular maturation, involves an integrated series of vascular activities, including inter alia, arteriovenous specification, vessel pruning, new vessel coverage by mature pericytes, and, in some tissues, the formation of a hierarchical network of vessels based on diameters. (9,10) Although angiogenesis stricto sensu has been extensively studied, especially in cancer, post-angiogenesis is not fully understood. In retina development or during skin wound repair, this process is characterized by a complex cascade of events involving an array of genes such as PDGF-BB/PDGF-R alpha signaling, which controls pericyte recruitment to the vessel wall, or increase in angiopoietin2/angiopoietin1 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of macrophages to wound healing and bone regeneration involves angiogenesis. In mouse models, macrophages positively influence angiogenesis by driving resolution of anti‐angiogenic wound neutrophils (Gurevich et al., ). Macrophages also contribute to wound healing by their expression of IL10.…”
Section: Preamblementioning
confidence: 99%
“…An effective angiogenic response is pivotal for both wound healing (Eming et al, 2014) and biomaterial integration (Spiller et al, 2015). Our previous work has indicated that proinflammatory macrophages expressing tumour necrosis factor α (tnfα) are critical in driving sprouting angiogenesis during tissue repair, but that macrophages must switch to an antiinflammatory, tnfα negative state at later stages to enable appropriate subsequent vessel remodelling and regression (Gurevich et al, 2018). We have used our suture implantation model to observe the dynamic changes that occur with respect to both tissue inflammation and angiogenesis during a FBR.…”
Section: Tissue Inflammation Is Exacerbated By Fbr and Induces The Fomentioning
confidence: 99%
“…We have developed a genetically tractable and translucent model of the FBR that allows for transgenic fluorescent marking of various cells and tissues, enabling the real-time visualisation of immune cell-foreign body interaction over time in a non-invasive manner (Witherel et al, 2017). Aside from external fibrin clot formation, most steps of mammalian wound repair appear to be well conserved in zebrafish and have previously been extensively characterised (Gurevich et al, 2018;Mathias et al, 2009;Renshaw et al, 2006;Richardson et al, 2013); all the initial tissue interactions that are believed to contribute to the development of FBR are known to be present. By fluorescently labelling leukocytes, inflammatory markers and blood vessels, we are able to study the dynamic activities of cells in response to the implanted biomaterials, observing the interactions between these cells and the subsequent fibrotic encapsulation, and how these interactions can be modulated to reduce fibrosis and improve integration of biomaterials.…”
Section: Introductionmentioning
confidence: 99%